Earthquake Nucleation Size: Evidence of Loading Rate Dependence in Laboratory Faults. Issue 1 (22nd January 2019) - Guérin‐Marthe, Simon; Nielsen, Stefan; Bird, Robert; Giani, Stefano; Di Toro, Giulio
Abstract: Recent Global Positioning System observations of major earthquakes such as the 2014 Chile megathrust show a slow preslip phase releasing a significant portion of the total moment (Ruiz et al., 2014, https://doi.org/10.1126/science.1256074 ). Despite advances from theoretical stability analysis (Rubin & Ampuero, 2005, https://doi.org/10.1029/2005JB003686 ; Ruina, 1983, https://doi.org/10.1029/jb088ib12p10359 ) and modeling (Kaneko et al., 2017, https://doi.org/10.1002/2016GL071569 ), it is not fully understood what controls the prevalence and the amount of slip in the nucleation process. Here we present laboratory observations of slow slip preceding dynamic rupture, where we observe a dependence of nucleation size and position on the loading rate (laboratory equivalent of tectonic loading rate). The setup is composed of two polycarbonate plates under direct shear with a 30‐cm long slip interface. The results of our laboratory experiments are in agreement with the preslip model outlined by Ellsworth and Beroza (1995, https://doi.org/10.1126/science.268.5212.851 ) and observed in laboratory experiments (Latour et al., 2013, https://doi.org/10.1002/grl.50974 ; Nielsen et al., 2010, https://doi.org/10.1111/j.1365-246x.2009.04444.x ; Ohnaka & Kuwahara, 1990, https://doi.org/10.1016/0040-1951(90)90138-X ), which show a slow slip followed by an acceleration up to dynamic rupture velocity. However, further complexity arises from the effect of (1) rate of shear loading and (2) inhomogeneities on the fault surface. In particular, we show that when the loading rate is increased from 10 −2 to 6 MPa/s, the nucleation length can shrink by a factor of 3, and the rupture nucleates consistently on higher shear stress areas. The nucleation lengths measured fall within the range of the theoretical limits L b and L ∞ derived by Rubin and Ampuero (2005, https://doi.org/10.1029/2005JB003686 ) for rate‐and‐state friction laws. Key Points: The nucleation length decreases with loading rate, implying that smaller‐size asperities clusters can be triggered by accelerated slip The nucleation position localizes on high coulomb stress patches with small‐scale inhomogeneities at high loading rates The measured nucleation length of laboratory earthquakes falls into the range predicted by numerical and theoretical studies